Embedding VRAD (Virtual Reality Aided Design) in Architectural Pedagogy - Tedjosaputro, Mia Ardiati; Mareta, Sannia (Proceedings of IEEE International Conference on Teaching, Assessment, and Learning for Engineering (Online), 2021)
As architectural pedagogy slowly transitions to embed VRAD to its existing curriculum, educators often face the lack of a scaffolded and structured approach. This paper draws reflections from the current project, V-ROOM (Virtual Classroom) to build a baseline of how to embed the use of VR particularly in architectural education. We collected preliminary data from undergraduate architecture students to further seek understanding from students' perspectives. The suggested 6 weeks of an elective module's plan is proposed to be a starting point for considerations.